Systematic Review: The Impact Analysis and Implementation Policies of Exclusive Breastfeeding Programs - Meita Tyas Nugrahaeni; Oedojo Soedirham (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: Health promotion is an effort to improve the society's ability in order to make people empower themselves. Exclusive breastfeeding/ASI eksklusif is the practice of giving breast milk to infants for the first six months of life (without any additional food or water) a preventive intervention that addresses the single greatest potential impact on child mortality. Objective: To analyze the impact of the availability and unavailability of program policy that support exclusive breastfeeding in improving the implementation of exclusive breastfeeding policy. Method: The method used in this research was a systematic review technique. The process of searching for articles through Sagepub, Google, and Google Scholar. The keywords used were breastfeeding policy, breastfeeding policy and health promotion, breastfeeding health promotion, workplace breastfeeding policy, and maternity leaves starting from February 20, 2020, to April 15, 2020, and found 153 articles which were then sorted into 35 articles. The articles discussed the implementation of the exclusive breastfeeding program (10), the exclusive breastfeeding policy (12), and the impacts arising from the exclusive breastfeeding policy (13) with articles in Indonesian (10) and English (25). Results: The found policy that have not been implemented by the Indonesian government are policies that adopt the latest version of The International Code of Marketing of Breas Milk Substitutes. Weak implementation of follow-up on sanctions and fines if it violates applicable policy. Conclusion: The exclusive breastfeeding program carried out by Indonesia is still in the scope of classes for pregnant women, companion groups, exclusive breastfeeding socialization, and breastfeeding motivator training. Social, economic, and cultural factors are other supporting factors related to exclusive breastfeeding success.